Comparison of the Fecal Microbiota of Horses with Intestinal Disease and Their Healthy Counterparts - Taemook Park; Heetae Cheong; Jungho Yoon; Ahram Kim; Youngmin Yun; Tatsuya Unno (Veterinary Sciences, 2021)
(1) Background: The intestinal microbiota plays an essential role in maintaining the host’s health. Dysbiosis of the equine hindgut microbiota can alter the fermentation patterns and cause metabolic disorders. (2) Methods: This study compared the fecal microbiota composition of horses with intestinal disease and their healthy counterparts living in Korea using 16S rRNA sequencing from fecal samples. A total of 52 fecal samples were collected and divided into three groups: horses with large intestinal disease (n = 20), horses with small intestinal disease (n = 8), and healthy horses (n = 24). (3) Results: Horses with intestinal diseases had fewer species and a less diverse bacterial population than healthy horses. Lactic acid bacteria, Lachnospiraceae, and Lactobacillaceae were overgrown in horses with large intestinal colic. The Firmicutes to Bacteroidetes ratio (F/B), which is a relevant marker of gut dysbiosis, was 1.94, 2.37, and 1.74 for horses with large intestinal colic, small intestinal colic, and healthy horses, respectively. (4) Conclusions: The overgrowth of two lactic acid bacteria families, Lachnospiraceae and Lactobacillaceae, led to a decrease in hindgut pH that interfered with normal fermentation, which might cause large intestinal colic. The overgrowth of Streptococcus also led to a decrease in pH in the hindgut, which suppressed the proliferation of the methanogen and reduced methanogenesis in horses with small intestinal colic.